Selected Miticides for Use on Ornamental Plants - Robert H. Stamps; Lance S. Osborne (EDIS)
ENH1118, an 11-page fact sheet by Robert H. Stamps and Lance S. Osborne, provides an overview of the main mite pests of ornamental plants, detection, and control. Includes references and tables listing miticides and manufacturers/distributors. Published by the UF Department of Environmental Horticulture, April 2009.